The Disruptive Power of Massive Open Online Course (MOOC) - Richard Hannis, Ansah; Ezeh, Ogechukwu Vincentia; Tan*, Seng Teck; Shahryar, Sorooshian (2020)
While MOOCs (Massive open online courses) have ignited debate in both academics and practical spheres of learning, there seem to be an absence of integrated approach for ethical conduct, as well as for course design, management, and certification. This paper remarks that systematic approaches, models and best practices for designing, delivering and managing MOOCs would offer a solution to dealing with the technological and pedagogical issues. A few cases of insights have been highlighted for developing and maintaining the real value within specific institutional strategies and implementation. Moreover, a call is made for scientific studies that would unveil comprehensive strategies to reap the full potentials of MOOCs. This article is expected to shed light on the complexities of the MOOCs system as well as to support the development of an ethical and unified discipline, in which all MOOCs developers and institutions are accountable.